Preparation method of MXene / AgNWs fiber membrane, fiber membrane electrode plate and sleep detection equipment
Through the preparation method of MXene/AgNWs fiber membrane, the problem of insufficient wearable fabric sensors in wearable comfort and physiological signal monitoring accuracy is solved, and the high breathability, conductivity and comfort of the fiber membrane electrode sheet is achieved, which is suitable for sleep Monitoring equipment improves the stability and accuracy of monitoring data.
Patent Information
- Application Number
- CN202411422742.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
Existing wearable fabric sensors have problems with insufficient wear comfort and physiological signal monitoring in health monitoring and sleep detection, especially in the face of daily activities and in the face of tolerance and foreign body sensation in special environments.
Using the preparation method of MXene/AgNWs fiber membrane, fiber membrane electrode sheets with one-way guide wettability, breathability and conductivity are prepared by the construction of the hydrophilic/hydrophobic layer of the fiber membrane and the synergistic effect of conductive materials, and used in sleep monitoring equipment. The electrodes, combined with plasma equipment processing and spraying technology, form electrode sheets with good adhesion performance and comfort.
It realizes good adhesion performance and wear comfort of the fiber membrane, while improving conductivity and sensitivity, ensuring the signal stability and accuracy of the sleep monitoring equipment during long-term use, and reducing the retention of sweat in the fiber membrane. Improves wear comfort and fidelity of monitoring data.
Smart Images

Figure CN119287659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of conductive textiles, and in particular to a method for preparing a MXene / AgNWs fiber membrane, a fiber membrane electrode sheet and a sleep detection device. Background Art
[0002] At present, wearable fabric sensors have attracted widespread attention due to their huge application potential in health monitoring, sports tracking, and human-computer interaction. Compared with rigid electronic components, the fabric has good flexibility, breathability, and skin-friendliness, which can reduce the strange feeling when worn and monitor the human body's physiological signals such as heart rate, blood pressure, temperature, and movement status in real time. In order to adapt to practical applications in daily activities and special environments, wearable fabric sensors need to have good wearing comfort, excellent physiological signal monitoring performance, and good tolerance to external environments such as sweat, stains, and corrosive liquids.
[0003] On the other hand, as an alternative to complex-connected polysomnography equipment, wearable monitoring systems can achieve convenient and comfortable detection and analysis at home or in hospitals. In order to simulate daily human conditions, they have high requirements for the feeling of no foreign body and comfort when the equipment is worn.
[0004] Therefore, it is an important challenge to develop a wearable device that has good moisture conduction and breathability, keeps the human body comfortable, and can accurately monitor human muscles, heart rate, and movement posture through subtle changes in the body. Summary of the invention
[0005] In order to solve the above problems and overcome the shortcomings of the prior art, the present invention provides a method for preparing a MXene / AgNWs fiber membrane, the preparation method comprising:
[0006] Step 1: Fiber membrane treatment
[0007] The fiber membrane is immersed in a cleaning solution to remove impurities, and the surface of the immersed fiber membrane is rinsed with deionized water and dried to obtain a dried fiber membrane;
[0008] Step 2: Surface modification
[0009] Using a plasma device to hydrophilize the fiber membrane dried in step 1 to obtain a hydrophilic fiber membrane;
[0010] Step 3: MXene treatment
[0011] The hydrophilic fiber membrane obtained in step 2 is immersed in a MXene dispersion, and then dried to obtain a MXene fiber membrane;
[0012] Step 4: AgNWs processing
[0013] The AgNWs solution is sprayed on the surface of the MXene fiber membrane obtained in step three to obtain a MXene / AgNWs fiber membrane.
[0014] Specifically, in step 1, the fiber membrane is a TPU fiber membrane produced by electrospinning.
[0015] Specifically, in step 2, the plasma equipment treatment time is 15min-20min, in step 3, the concentration of MXene dispersion is 10mg / mL, the immersion time is 25min, and after immersion, it is placed in a 60°C vacuum drying oven for drying for 20min. In step 4, the concentration of sprayed AgNWs solution is 1wt%, and the spraying time is 30s-40s.
[0016] Specifically, the preparation method further comprises:
[0017] Step 5: Constructing the hydrophilic / hydrophobic layer
[0018] Spray ZnO solution on one side of the MXene / AgNWs fiber membrane obtained in step 4 to form a ZnO micro-nano fiber morphology, and spray PDMS coating on the surface of the ZnO micro-nano fiber morphology to form a hydrophobic surface; spray SiO2 on the other side of the fiber membrane to form a hydrophilic surface.
[0019] Specifically, the concentration of ZnO is 1 wt %, the concentration of PDMS is 0.5 wt %, and the concentration of SiO 2 is 0.5 wt %.
[0020] A fiber membrane electrode sheet comprises a fiber membrane and an electrode buckle. The fiber membrane is a single-layer structure. The hydrophilic surface of the fiber membrane is coated with an adhesive material to form an adhesive layer. A conductive buckle is arranged at the center of the other side of the fiber membrane.
[0021] Specifically, the adhesiveness of the fiber membrane electrode sheet gradually weakens from the central electrode to the surrounding areas.
[0022] A sleep monitoring device comprises a head host, a monitoring watch and a blood oxygen probe. The head host comprises a signal acquisition module, a brain electromyography sensor, a pulse rate sensor, a body movement sensor and a fabric headband. The brain electromyography sensor comprises 7 fiber membrane electrodes for collecting real-time brain electroencephalography and electromyography signals. The blood oxygen probe is used to collect blood oxygen saturation physiological signals. The monitoring watch is respectively connected to the head host and the blood oxygen probe signals to store and process the physiological signals.
[0023] Specifically, the fiber membrane electrode sheet includes: a GND electrode pasted at the center of the eyebrows, Fp1 and Fp2 electrodes pasted at the forehead, A1 and A2 reference electrodes pasted at the left and right ears, and S1 and S2 electromyographic electrodes pasted at the mandibular mentalis muscles.
[0024] Advantages
[0025] The MXene / AgNWs fiber membrane prepared by the present invention has a hydrophilic one side, fits the human body, and has good unidirectional moisture conductivity; the other side is hydrophobic, has good hydrophobic and self-cleaning effects, and has good air permeability, so that the human body maintains good wearing comfort; through the synergistic effect of the conductive material, the fiber membrane obtains good conductivity and sensitivity; by utilizing the synergistic cooperation of the fiber membrane and the adhesive layer, the electrode sheet not only has good adhesive properties, but also is not tight after being attached to the skin, and has good comfort when worn. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the contact angle of the surface of the MXene / AgNWs fiber membrane prepared in the present invention;
[0027] Figure 2 This is a graph showing the relationship between strain and stress of the MXene / AgNWs fiber membrane prepared in the present invention;
[0028] Figure 3 This is a trend chart of the monitoring report of the fiber membrane electrode sheet of the present invention applied to PSG;
[0029] Figure 4 It is a structural schematic diagram of the sleep detection device of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] A method for preparing a MXene / AgNWs fiber membrane comprises the following steps:
[0032] Step 1: Fiber membrane treatment
[0033] The fiber membrane is immersed in a cleaning solution. In the present invention, the fiber membrane is immersed in a 30 vol% ethanol solution for 25 minutes to remove the chemical substances on the surface. Then, the immersed fiber membrane surface is rinsed with deionized water and placed in a 60°C vacuum drying oven for 20 minutes to obtain a dry spinning fiber membrane for use.
[0034] Step 2: Surface modification
[0035] The fiber membrane dried in step one is hydrophilically treated for 15-20 minutes using plasma equipment to obtain a hydrophilic fiber membrane. Since most synthetic fibers are hydrophobic, direct dipping and coating with conductive materials has poor bonding effect, and the conductive material cannot be completely loaded on the fiber surface. After treatment with plasma equipment, the fiber membrane surface contains a large number of hydrophilic functional group hydroxyls, and the fiber membrane changes from hydrophobic to hydrophilic. The roughness of the fiber surface is also significantly increased, providing more attachment sites for the conductive material.
[0036] Step 3: MXene treatment
[0037] The hydrophilic fiber membrane obtained in step 2 was immersed in 10 mg / mL MXene dispersion for 25 min, and then placed in a 60°C vacuum drying oven for 20 min to obtain a MXene fiber membrane.
[0038] Step 4: AgNWs processing
[0039] The surface of the MXene fiber membrane obtained in step three was sprayed with 1 wt% AgNWs solution, with a spraying time of 30 s to 40 s and a rate of 5 mL / min to obtain a MXene / AgNWs fiber membrane.
[0040] Step 5: Constructing the hydrophilic / hydrophobic layer
[0041] One side of the MXene / AgNWs fiber membrane obtained in step 4 was sprayed with 1wt% ZnO solution to construct the ZnO micro-nano fiber morphology, and then 0.5wt% PDMS coating was sprayed at a rate of 5mL / min for 30s to form a hydrophobic surface; the other side of the MXene / AgNWs fiber membrane was sprayed with 0.4wt% SiO2 solution at a rate of 5mL / min for 30s to form a hydrophilic surface, so that one side of the MXene / AgNWs fiber membrane has good hydrophobicity and the other side has hydrophilicity, forming a unidirectional moisture conduction property. The hydrophilic side can quickly absorb sweat and discharge it from the other side, reducing the residence of sweat inside and on the surface of the fiber.
[0042] Gas permeability of MXene / AgNWs fiber membrane electrodes;
[0043] In actual use, the air permeability of the fiber membrane is an important indicator that directly affects the comfort of wearing. According to the GB / T5453-1997 "Determination of Air Permeability of Fiber Membranes" standard, the constant pressure difference flow measurement method is used to evaluate the air permeability of MXene / AgNWs fiber membrane electrodes.
[0044] Table 1 Air permeability of MXene / AgNWs fiber membrane
[0045]
[0046] As shown in Table 1, under a pressure of 100Pa, the air permeability of the MXene / AgNWs fiber membrane is 70.1mm / s. When the pressure increases by 50Pa, the air permeability of the MXene / AgNWs fiber membrane also increases accordingly. Under a pressure of 300Pa, the air permeability of the MXene / AgNWs fiber membrane reaches 190.2mm / s, indicating that the MXene / AgNWs fiber membrane has good air permeability. At the same time, it shows that the fiber membrane has good stability under different air pressure environments and has good comfort when worn on the body.
[0047] Hydrophobic properties of MXene / AgNWs fiber membranes;
[0048] like Figure 1 As shown, for one side of the MXene / AgNWs fiber membrane containing ZnO and PDMS, using a contact angle measurement instrument, it can be observed that a 10uL droplet is attached to the hydrophobic surface of the MXene / AgNWs fiber membrane, presenting a spherical state, without wetting the MXene / AgNWs fiber membrane. The water contact angle of the MXene / AgNWs fiber membrane reaches 158°, showing a good hydrophobic effect, making it difficult for sweat, stains, etc. on the outer surface of the fiber membrane to penetrate into the fiber membrane and affect the conductivity of the fiber membrane and other functions, and the hydrophilic / hydrophobic properties of one side are used to form rapid moisture conduction, reducing the influence of sweat on the performance of the fiber membrane.
[0049] Mechanical properties of MXene / AgNWs fiber film electrodes;
[0050] like Figure 2 As shown, the breaking strength and breaking elongation of the MXene / AgNWs fiber membrane electrode were tested by a universal tensile testing machine. The experimental test was based on the GB / T3923.1-2013 standard (strip method), which showed the relationship between the strain and stress of the MXene / AgNWs fiber membrane electrode. From the strain and stress curve of the MXene / AgNWs fiber membrane electrode, it can be obtained that its breaking elongation is 242.4% and the breaking strength is 3.7 MPa, which proves that the MXene / AgNWs fiber membrane electrode has good elasticity and high strength.
[0051] Example 1
[0052] According to the preparation method of the MXene / AgNWs fiber membrane, the MXene dispersion and the AgNWs solution are produced by Jilin Yiyi Technology Co., Ltd.: 30 mg / mL MXene dispersion and 10 wt% AgNWs solution, respectively prepared by dilution method to prepare 10 mg / mL MXene dispersion and 1 wt% AgNWs solution:
[0053] The fiber membrane in step 1 is a 4 cm×4 cm electrospun TPU fiber membrane;
[0054] In step 2, the fiber membrane is treated with a plasma device for 15 minutes;
[0055] In step 4, the AgNWs solution is sprayed for 40 seconds at a rate of 5 mL / min to prepare the fiber membrane.
[0056] Example 2
[0057] According to the above-mentioned method for preparing MXene / AgNWs fiber membrane, the difference from Example 1 is that:
[0058] The treatment time of the plasma equipment in step 2 is 20 minutes; and the fiber membrane is prepared.
[0059] Example 3
[0060] According to the above-mentioned method for preparing MXene / AgNWs fiber membrane, the difference from Example 1 is that:
[0061] In step 4, the AgNWs solution is sprayed for 30 seconds; and the fiber membrane is prepared.
[0062] Comparative Example 1
[0063] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0064] The fiber membrane in step 1 was replaced with 4 cm×4 cm NWF polyurethane nonwoven fabric; and subsequent preparation was performed.
[0065] Polyurethane non-woven fabric is selected because it has good mechanical strength and tensile properties, large pores in the fiber structure, good air permeability, and a contact angle of 70°-90°, showing hydrophilicity.
[0066] Comparative Example 2
[0067] According to the above-mentioned method for preparing MXene / AgNWs fiber membrane, the difference from Example 1 is that:
[0068] The treatment time of the plasma equipment in step 2 is 5 minutes; and the fiber membrane is prepared.
[0069] Comparative Example 3
[0070] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0071] The material modification method in step 2 is replaced by: immersing the dried TPU fiber membrane in DA solution, reacting it in a water bath oscillator at 35°C and a speed of 160 rpm for 24 hours, and then obtaining a PDA-modified TPU fiber membrane; and preparing the fiber membrane.
[0072] PDA can quickly form a film on the surface of the material, which contains a large number of hydrophilic hydroxyl and amino functional groups, which can improve the hydrophilicity and chemical multifunctionality of the material surface.
[0073] Comparative Example 4
[0074] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0075] Replace the fiber membrane in step 1 with 4 cm × 4 cm NWF polyurethane non-woven fabric;
[0076] The material modification method in step 2 is replaced by: immersing the dried TPU fiber membrane in DA solution, reacting it in a water bath oscillator at 35°C and a speed of 160 rpm for 24 hours, and then obtaining a PDA-modified TPU fiber membrane; and preparing the fiber membrane.
[0077] Comparative Example 5
[0078] According to the above-mentioned method for preparing MXene / AgNWs fiber membrane, the difference from Example 1 is that:
[0079] In step 4, the AgNWs solution is sprayed for 20 seconds; and the fiber membrane is prepared.
[0080] Comparative Example 6
[0081] According to the above-mentioned method for preparing MXene / AgNWs fiber membrane, the difference from Example 1 is that:
[0082] In step 4, the AgNWs solution is sprayed for 50 seconds; and the fiber membrane is prepared.
[0083] Comparative Example 7
[0084] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0085] The spraying of AgNWs solution in step 4 is replaced by: immersing the MXene fiber membrane in 1 wt % AgNWs solution to obtain a MXene / AgNWs fiber membrane; and preparing the fiber membrane.
[0086] Comparative Example 8
[0087] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0088] The spraying of AgNWs solution in step 4 was replaced by: immersing the MXene fiber membrane in a 10 mg / ml MWNTs solution for 25 min, and then drying; preparing the fiber membrane.
[0089] MWNTs multi-walled carbon nanotubes are selected because they have good conductivity and excellent mechanical properties. Attaching them to the surface of the material can improve the conductivity of the fiber.
[0090] Comparative Example 9
[0091] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0092] Replace the fiber membrane in step 1 with 4 cm × 4 cm NWF polyurethane non-woven fabric;
[0093] The material modification method in step 2 is replaced by: immersing the dried TPU fiber membrane in DA solution, reacting it in a water bath oscillator at 35°C and a speed of 160 rpm for 24 hours, and then obtaining a PDA-modified TPU fiber membrane;
[0094] The spraying of AgNWs solution in step 4 was replaced by: immersing the MXene fiber membrane in the MWNTs solution for 25 min, and then drying; preparation was performed.
[0095] Comparative Example 10
[0096] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0097] In step five: spray SiO2 solution on one side of the MXene / AgNWs fiber membrane, and then spray 0.5wt% PDMS coating to form a hydrophobic surface; spray ZnO on the other side to form a hydrophilic surface; and prepare the fiber membrane.
[0098] The products obtained in the above examples and comparative examples were functionally verified, and their conductivity, sensitivity and moisture permeability were tested respectively.
[0099] Experimental Example 1
[0100] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0101] In step 2, the fiber membrane is prepared without modifying the fiber membrane; and the conductivity of the fiber membrane is tested.
[0102] Experimental Example 2
[0103] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0104] Step 3: After obtaining the dried MXene fiber membrane, no subsequent treatment is performed; the conductivity of the fiber membrane is tested.
[0105] Experimental Example 3
[0106] According to the preparation method of MXene / AgNWs fiber membrane in Example 1, the difference from Example 1 is that:
[0107] After the MXene fiber membrane obtained by immersion once in step 3, the MXene fiber membrane is immersed in the MXene dispersion again for 25 minutes, and no subsequent treatment is performed after drying; the conductivity of the fiber membrane is tested.
[0108] The experimental results of the embodiments, comparative examples and experimental examples are shown in Table 2.
[0109] Table 2
[0110]
[0111] It can be seen from the data in Table 2 that after the hydrophobic TPU spun fiber membrane is treated with a plasma device, the conductivity of the fiber membrane is significantly improved. Since the contact angle of the TPU electrospun fiber membrane is greater than 90° under normal conditions, it shows hydrophobicity and it is difficult for conductive materials to adhere to the surface. Therefore, the conductivity of the MXene fiber membrane that has not been treated with plasma in Experimental Example 1 is only 10.6S / m. After 15 minutes of treatment, the conductivity of the MXene / AgNWs fiber membrane is increased to 2233.2S / m. When the treatment time exceeds 15 minutes, the sensitivity of the MXene / AgNWs fiber membrane decreases to a certain extent. When the modification method is replaced with PDA modification, the conductivity, sensitivity and moisture permeability of the fiber membrane are significantly reduced compared with Example 1.
[0112] By changing the time of spraying AgNWs, when spraying for 20 seconds, the conductivity of the MXene / AgNWs fiber membrane electrode is 1123.2S / m and the sensitivity is 1276GF. With the increase of spraying time, the conductivity and sensitivity of the MXene / AgNWs fiber membrane increase. After 40 seconds of spraying, the MXene / AgNWs fiber membrane shows good conductivity of 2233.2S / m. When the spraying time exceeds 40 seconds, the sensitivity and moisture permeability of the MXene / AgNWs fiber membrane decrease significantly. Further, the spraying of AgNWs solution is replaced by immersion. Compared with the spraying experimental results, the conductivity, sensitivity and moisture permeability are greatly reduced. After replacing the AgNWs solution with MWNTs multi-walled carbon nanotube solution, the conductivity, sensitivity and moisture permeability are much lower than those of the fiber membrane sprayed with AgNWs.
[0113] When polyurethane non-woven fabric is used to replace TPU spun fiber membrane, good conductivity and sensitivity are not obtained after plasma treatment or PDA modification. Studies have found that there is a discontinuous change between the improvement of the hydrophilicity of the fiber material itself and the conductive properties of the material. After replacing the fiber membrane, the conductive properties not only did not increase or remain unchanged, but decreased compared to the TPU spun fiber membrane.
[0114] The moisture permeability of the fiber membrane is also one of the important indicators that affect wearing comfort. Experiments have shown that compared with Examples 1, 2, and 3, the type of fiber membrane, the fiber modification method, and the type and method of combining conductive materials in the comparative example will cause the moisture permeability of the fiber membrane to decrease. Moreover, after the surface-modified ZnO and SiO2 in the MXene / AgNWs fiber membrane are replaced with each other, the unidirectional moisture permeability of the fiber membrane is significantly reduced.
[0115] Example 4
[0116] A fiber membrane electrode sheet for a sleep monitoring device. The fiber membrane electrode sheet is a MXene / AgNWs fiber membrane manufactured by the above-mentioned MXene / AgNWs fiber membrane preparation method. The fiber membrane electrode sheet includes a fiber membrane and an electrode buckle. The fiber membrane is a single-layer structure. The hydrophilic surface of the fiber membrane is coated with an adhesive material to form an adhesive layer. A conductive buckle is arranged at the center of the other side of the fiber membrane. When in use, the adhesive layer is adhered and fixed with one side facing the skin. The conductive buckle is connected to a detection device through a wire to monitor human physiological data.
[0117] The adhesive layer of the fiber membrane electrode sheet gradually weakens the adhesion of the electrode sheet from the central electrode to the surrounding areas. Taking a circular electrode sheet and the adhesive selected from Haishi Hainuo adhesive medical gel as an example, the radius of the electrode sheet is R, and the center position accounting for 10% of the area of the electrode sheet, with a radius of about ≤0.3R, is taken as the central area, and is fully covered with adhesive material to ensure the adhesion firmness and the accuracy of the center measurement positioning; the adhesion of the area with a radius of 0.3R-0.6R outside the center area, accounting for about 28% of the total area of the electrode sheet, is reduced to 70%-80%; the adhesion of the area of 0.6R-0.8R outside the outer side, accounting for about 30% of the total area of the electrode sheet, is reduced to 40%-50%; the adhesion of the area closest to the edge 0.8RR, accounting for about 32% of the total area of the electrode sheet, is reduced to 10%-20%, so that the electrode sheet can be naturally peeled off with a slight force.
[0118] The adhesion of the electrode sheet can be adjusted by changing the type of adhesive, the sparseness of the adhesive or by using an intermittent arrangement of the adhesive. Preferably, the adhesive adopts a mesh structure, and the adhesion of the adhesive layer is controlled by the density of the mesh structure.
[0119] The electrode sheet in Example 4 and other electrode sheets were respectively used in PSG polysomnography experiments to test their effective measurement time under different conditions, wherein the electrode sheet comprises:
[0120] 1. The fiber membrane electrode sheet in Example 4;
[0121] 2. The product obtained in Comparative Example 1 is used as a fiber membrane and an electrode sheet is made by the above method;
[0122] 3. The product obtained in Comparative Example 7 is used as a fiber membrane and an electrode sheet is made in the above manner;
[0123] 4. The product obtained in Comparative Example 10 is used as a fiber membrane and an electrode sheet is made by the above method;
[0124] 5. The fully adhesive disposable wet-gel ECG electrodes purchased from the market comply with ISO10993-10:2010 standard; the test results are shown in Table 3 below.
[0125] Table 3
[0126]
[0127]
[0128] like Figure 3 As shown in Table 3, the effective measurement time of the fiber membrane electrode sheet of the present invention in the PSG experiment is 10 hours, that is, it maintains good adhesion performance throughout the experiment. According to the trend chart, it can be seen that the myoelectric, electroencephalographic and other indicator signals of the subjects in the middle and late stages of the measurement are accurate and clear, and accurate sleep information can be obtained after equipment analysis. The measurement time of electrode sheets 2-5 is shorter than that of electrode sheet 1. During the measurement process, problems such as weak signal and poor stability occur, resulting in a decrease in the accuracy of sleep data.
[0129] Taking into account that the fiber membrane electrode sheet needs to be in direct contact with the skin, especially for EEG acquisition electrodes directly attached to the face, head and other areas, and because the face is rich in peripheral nerves and muscles, common medical adhesives will make the skin tight, reducing comfort and making it difficult for the human body to maintain the same physiological state as in normal state during physiological monitoring, resulting in distortion of monitoring data; if the viscosity of the adhesive is reduced, human sweating during the pasting process will further cause the viscosity of the adhesive to decrease, causing the electrode sheet to shift or even fall off during muscle activity. However, in the present invention, even on the basis of setting the viscosity of the adhesive to gradually weaken all around, the firmness of the electrode sheet after being attached to the skin is still maintained, and the effective measurement time is more than 10 hours. After adjusting the adhesiveness, the electrode sheet is not tight, reducing the foreign body sensation after being attached to the skin, and increasing the fidelity of the physiological recording data.
[0130] Example 5
[0131] A sleep monitoring device using a MXene / AgNWs fiber membrane electrode sheet. The device adopts a portable polysomnogram that complies with the PSG international standard AASM and R&K, and uses the above-mentioned MXene / AgNWs fiber membrane electrode sheet as an electrode. It includes a head host, a monitoring watch and a blood oxygen probe. The head host includes a signal acquisition module, a brain electromyography sensor, a pulse rate sensor, a body movement sensor and a fabric headband. The brain electromyography sensor includes 7 fiber membrane electrode sheets for collecting real-time brain electroencephalogram and electromyography signals. The blood oxygen probe is used to collect blood oxygen saturation physiological signals. The monitoring watch is connected to the head host and the blood oxygen probe signals respectively to store and process the physiological signals.
[0132] The fiber membrane electrode sheet includes: a GND electrode pasted on the center of the eyebrows, Fp1 and Fp2 electrodes pasted on the forehead, A1 and A2 reference electrodes pasted behind the left and right ears, and S1 and S2 electromyographic electrodes pasted on the mandibular mental muscles. The seven fiber membrane electrodes can obtain accurate sleep physiological data with fewer test units. At the same time, the use of fiber membrane electrodes reduces the foreign body sensation caused by hard electrodes and sticky sheets to the human body during sleep, which affects the normal sleep quality.
[0133] The head host can be worn on the head through a fabric headband. The brain electromyography sensor, pulse rate sensor, and body movement sensor are respectively connected to the signal acquisition module. Seven fiber membrane electrodes monitor EEG and EMG signals. The pulse sensor is set close to the head artery when the host is worn to monitor the pulse signal. The head host can also be equipped with a Bluetooth module to wirelessly transmit brain electromyography signals, pulse signals, and body movement signals to the monitoring watch. At the same time, the blood oxygen probe is worn on the finger, and the blood oxygen saturation data can be transmitted to the monitoring watch via Bluetooth or a data terminal.
[0134] The monitoring watch includes a collection and processing module, which interprets the physiological information collected by the head host and the blood oxygen probe and outputs a sleep monitoring report. The monitoring watch can also include a display, a switch, a battery and a charging unit, etc., and can also export the sleep monitoring data to a computer to complete manual interpretation of the data and output a complete sleep monitoring report.
[0135] Preferably, the fabric headband is a blended fabric containing 30-40% viscose fiber and 3-14% spandex, and the remaining materials can be cotton or polyester fiber. The viscose fiber keeps the headband breathable and has good antistatic properties. After blending with spandex, the headband has good elasticity, and the fabric is smooth and close to the skin after wearing. The viscose fiber content is set to less than 40% and 3-14% spandex material is used, so that the fabric maintains elasticity and flatness after repeated use and cleaning, thereby improving the durability of the headband. The spandex material in the headband has good elasticity and maintains good toughness at 3-14%, so that the head host is not easy to be displaced during head movements after being worn, thereby improving the stability of the equipment. In addition, due to the good stability of the head host, the length of the electrode sheet wire can be further reduced according to the human body shape to avoid the unfixed wire from swinging during head movements, affecting the equipment measurement.
[0136] like Figure 4 As shown, the headband adopts a double fixed structure, and two fabric headbands are used to fix the corresponding forehead position and the upper forehead position respectively, so as to avoid the stuffiness caused by the whole piece covering a large area, and under the high elastic effect of the fabric headband, the stability of the head host after wearing is improved; and it is tested with the existing PSG polysomnography: 2 participants are selected to wear the existing polysomnography and the sleep monitoring device of Example 5 respectively, wherein both devices adopt the electrode sheet in Example 4 of the present application, and sleep monitoring is performed and sleep data is recorded for 5 consecutive nights, and then after a week of rest, the two participants exchange devices, and sleep monitoring is performed and sleep data is recorded for 5 consecutive nights, and finally 10 sleep data of each person wearing the existing polysomnography and the sleep monitoring device of Example 5 are obtained, and the fluctuation of sleep data between multiple experiments of the two devices is compared, especially for key sleep parameters such as REM sleep cycle, number of awakenings, sleep efficiency, etc.
[0137] After testing, it was found that when wearing a traditional polysomnography for sleep monitoring experiments, the deviation in the number of awakenings between multiple tests of two participants was greater than 2 times, and the deviation in sleep efficiency (actual sleep time / total time in bed) was greater than 5%, especially the deviation in sleep efficiency between the first sleep record and the subsequent records was 7.5%; while the sleep monitoring equipment using Example 5 had significantly higher data stability during sleep recording than the existing polysomnography equipment, the deviation in the number of awakenings was less than 2 times, and the deviation in sleep efficiency was less than 3%.
[0138] This embodiment uses a host headband, a wristwatch, and a blood oxygen probe, as well as fiber membrane electrodes to reduce the foreign body and pressure caused by the sleep monitoring equipment when the human body is sleeping. The device can be used to monitor sleep in a daily home environment, and sleep data that conforms to the daily sleep state can be obtained to improve the accuracy of sleep quality monitoring.
[0139] The above-mentioned embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the embodiments of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. All obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a MXene / AgNWs fiber membrane, characterized in that: The preparation method comprises: Step 1: Fiber membrane treatment The fiber membrane is immersed in a cleaning solution to remove impurities, and the surface of the immersed fiber membrane is rinsed with deionized water and dried to obtain a dried fiber membrane; Step 2: Surface modification Using a plasma device to hydrophilize the fiber membrane dried in step 1 to obtain a hydrophilic fiber membrane; Step 3: MXene treatment The hydrophilic fiber membrane obtained in step 2 is immersed in a MXene dispersion, and then dried to obtain a MXene fiber membrane; Step 4: AgNWs processing The AgNWs solution is sprayed on the surface of the MXene fiber membrane obtained in step three to obtain a MXene / AgNWs fiber membrane.
2. The preparation method according to claim 1, characterized in that: The fiber membrane in step 1 is a TPU fiber membrane produced by electrostatic spinning.
3. The preparation method according to any one of claims 1 or 2, characterized in that: The plasma equipment treatment time in step 2 is 15 min-20 min, the MXene dispersion concentration in step 3 is 10 mg / mL, the immersion time is 25 min, and after immersion, it is placed in a 60° C. vacuum drying oven for drying for 20 min.
4. The preparation method according to claim 1, characterized in that: In the step 4, the concentration of the AgNWs solution sprayed is 1 wt % and the spraying time is 30 s to 40 s.
5. The preparation method according to claim 1, characterized in that: The preparation method further comprises: Step 5: Constructing the hydrophilic / hydrophobic layer Spray ZnO solution on one side of the MXene / AgNWs fiber membrane obtained in step 4 to form a ZnO micro-nano fiber morphology, and spray PDMS coating on the surface of the ZnO micro-nano fiber morphology to form a hydrophobic surface; spray SiO2 solution on the other side of the fiber membrane to form a hydrophilic surface.
6. The preparation method according to claim 5, characterized in that: The concentration of ZnO is 1 wt %, the concentration of PDMS is 0.5 wt %, and the concentration of SiO 2 is 0.5 wt %.
7. A fiber membrane electrode sheet, wherein the fiber membrane electrode sheet is made by the fiber membrane prepared by any one of the preparation methods of claims 5 and 6, characterized in that: The fiber membrane electrode sheet includes a fiber membrane and an electrode buckle. The fiber membrane is a single-layer structure. The hydrophilic surface of the fiber membrane is coated with an adhesive material to form an adhesive layer. A conductive buckle is arranged at the center of the other side of the fiber membrane.
8. The fiber membrane electrode sheet according to claim 7, characterized in that: The adhesive layer of the fiber membrane electrode sheet gradually weakens the adhesiveness of the electrode sheet from the central electrode to the surrounding areas.
9. A sleep monitoring device using the fiber membrane electrode sheet according to claim 8, characterized in that: It includes a head host, a monitoring watch and a blood oxygen probe. The head host includes a signal acquisition module, a brain electromyography sensor, a pulse rate sensor, a body movement sensor and a fabric headband. The brain electromyography sensor includes 7 fiber membrane electrodes for collecting real-time brain electroencephalography and electromyography signals. The blood oxygen probe is used to collect blood oxygen saturation physiological signals. The monitoring watch is respectively connected to the head host and the blood oxygen probe signals to store and process physiological signals.
10. The sleep monitoring device according to claim 9, characterized in that: The fiber membrane electrode sheet includes: a GND electrode pasted on the center of the eyebrows, Fp1 and Fp2 electrodes pasted on the forehead, A1 and A2 reference electrodes pasted behind the left and right ears, and S1 and S2 electromyographic electrodes pasted on the mandibular mentalis muscles.